2018
DOI: 10.1111/ecno.12122
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Monetary Policy in Inflation Targeting Open Economies

Abstract: This paper presents a simple framework for analysing the operation and effectiveness of monetary policy in open economies in the spirit of aggregative approaches that are the mainstay of intermediate macroeconomic theory. Combining standard macroeconomic relations with precepts from international finance, it provides new lessons for the conduct of monetary policy under inflation targeting. It first confirms the classic Mundell-Fleming result that monetary policy is only effective as a short run stabilization i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…They also reported that inflation targeting promotes stability in financial sectors. A review from inflation targeting open economies, Makin (2019) revealed that appropriate policy on inward strategy for productivity enhancement tends to control the pressure of inflation and price level in the medium term. On the Brazilian economy, Díaz-Roldán et al (2019) affirmed that fiscal rules and fiscal discipline under inflation targeting regime help in controlling the inflationary environment in Brazil.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…They also reported that inflation targeting promotes stability in financial sectors. A review from inflation targeting open economies, Makin (2019) revealed that appropriate policy on inward strategy for productivity enhancement tends to control the pressure of inflation and price level in the medium term. On the Brazilian economy, Díaz-Roldán et al (2019) affirmed that fiscal rules and fiscal discipline under inflation targeting regime help in controlling the inflationary environment in Brazil.…”
Section: Review Of the Literaturementioning
confidence: 99%